Patient Safety Culture, Knowledge and Effective Communication Effectively Increasing Reporting of Patient Safety Incidents - Novrifa, Hetzy; Mutiara, Rina; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: Patient safety culture is an important principle that must be implemented in an effort to create a safe and healthy hospital environment. The large number of patient safety incidents, which have not been reported completely, accurately and clearly, will be a phenomenon that can be detrimental to patients and hospitals in terms of service costs. Objective: The study aimed to determine the relationship between patient safety culture, knowledge and effective communication of nurses on reporting patient safety incidents at Tiara Bekasi Hospital. Method: The research method in this study uses a cross-sectional approach. Sample recruitment in this study used total sampling of 101 nurses. Result: The results of this research analysis show that there is a significant relationship between patient safety culture and reporting of patient safety incidents. There is a significant relationship between knowledge and reporting of patient safety incidents. There is a significant relationship between effective communication and patient safety incident reporting. The results of the multivariate analysis in this study show that patient safety culture is the most dominant variable. Conclusion: The conclusions in this study show that it is important for nurses to have patient safety culture, knowledge and effective communication so that they are appropriate in reporting patient safety incidents.